Calliophis bivirgatus (Blue Malaysian CoralSnake). DIET - ANDREW, GNANANANTHAM; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2025)
The note describes a predation event involving Calliophis bivirgatus in Malaysia.